Effects of decompressive craniectomy on brain tissue oxygen in patients with intracranial hypertension. Issue 4 (1st April 2003) - Jaeger, M; Soehle, M; Meixensberger, J
Abstract : This report examined the intraoperative course of partial pressure of brain tissue oxygen (Pti O2 ) and intracranial pressure (ICP) during surgical decompressive craniectomy for medically intractable intracranial hypertension due to diffuse brain swelling in three patients after severe subarachnoid haemorrhage and aneurysm coiling. The mean ICP decreased from 59 mm Hg to 10 mm Hg in a two step fashion, relating to bone flap removal and dural opening. Simultaneously, Pti O2 increased rapidly from 0.8 kPa (6 mm Hg) to 3.07 kPa (23 mm Hg). Pti O2 and ICP remained at non-critical ranges postoperatively. Despite these beneficial effects on ICP and Pti O2, the patients' clinical status remained poor with two in a persistent vegetative state and one dead.